Encouraging the subsistence artisan entrepreneurship in handicraft and creative contexts - Ferreira, Jéssica (2020)
Abstract Purpose – This study aims to establish a relationship between creative tourism and experiences in the traditional handicrafts of Barcelos (Portugal). Based on a qualitative approach, it also aims at analyzing the failures and absences from the tourist market by creating new proposals and responses to the demand. The conceptual framework of this study develops three proposals: first, to present new concepts and opportunities for the tourism market; second, to establish a direct relationship between the local traditional handicrafts, creative tourism and experiences; and finally, to promote traditions that add value to the local development. Design/methodology/approach – This study uses an ethnographic case analysis research design to investigate the propositions (ten in-depth interviews with technicians and artisans in Barcelos, Portugal). The key constructs are drawn from empirical research among handicraftsmen in which data analysis was carried out based on a qualitative analysis. Findings – The results suggest the experience, knowledge and importance of learning this dynamic in an entrepreneurship tourism perspective. Creative tourism and experiences are growing and strengthening the territories and consumer satisfaction in specific artisan, cultural and tourism entrepreneurship contexts. Research limitations/implications – This study fills a large gap in the territorial market, associating the knowledge of new concepts with the success of the tourism entrepreneurship. The findings provide solutions for helping handicraftsmen to improve their decision-making logic and increase the speed of market growth. There has been an increased emphasis on local and handmade goods that are linked to the culture and tourism of specific destinations. Originality/value – Tourism managers and artisan entrepreneurs can use the outcome of this study to gain in-depth understanding of customer experiences (i.e. consumers of local handicrafts) and develop effective marketing strategies and further stage the operational environment that can maximize customers’ perceived experiential value.